Pemeriksaan Fisik sebagai Upaya Deteksi Dini dan Pencegahan Penyakit Gagal Ginjal pada Siswa SMA Muhammadiyah Al Kautsar PK Kartasura - Ani Syafriati; Triastika Ayuk Setyaningsih; Rahmad Bagus Saifudin; Nasmah Min Salsa Billa; Muhammad Putra Ardiansyah; Salma Maulida Khoiriya; Nada Rizky Nur Hanifah; Nabila Lintang Dikmazari; laila sholaikhah indriani; Reeham farooq; Rossana Mutia Azzahra; Muhammad Reza Kurniawan; Noor fathima Thottungal; Marwan Ahmad; Hanifa Eka Rahmadani; Atrina Madina Suci; Calysta Vinella Ardhana; Ikhwan Muhana Rafif; Fara Dzulfi Aulia Pratama (Fakultas Kedokteran, Universitas Mulawarman, 2025)
Non-communicable diseases such as hypertension, diabetes mellitus, and chronic kidney disease are increasingly prevalent among young people due to unhealthy lifestyles. Early detection through simple health examinations in schools is an effective strategy to prevent chronic diseases. This community service activity aimed to conduct health screening as an early detection effort for chronic disease risk factors among 80 students of SMA Muhammadiyah Al Kautsar PK Kartasura. The methods included health education on healthy lifestyles, blood pressure measurement using a digital sphygmomanometer, body weight and height measurement to calculate Body Mass Index (BMI), and random blood glucose testing using a glucometer. The results showed that 80% of students had normal blood pressure, 12% were in the pre-hypertension category, and 8% were obese. Blood glucose examination revealed that 6% of students were in the borderline category (pre-diabetes) and 94% were within the normal range. These findings highlight the importance of early intervention through health education and regular screening. This program successfully increased students’ awareness of the importance of regular health checks and healthy lifestyle behaviors. Conclusion: Basic health screening at school can be an effective promotive and preventive effort to reduce the risk of chronic diseases among adolescents.